2016
DOI: 10.1002/1873-3468.12075
|View full text |Cite
|
Sign up to set email alerts
|

Novel motif in calcineurin catalytic subunit is required for septal localization of calcineurin in Aspergillus fumigatus

Abstract: Calcineurin heterodimer, comprised of the catalytic (CnaA) and regulatory (CnaB) subunits, localizes at the hyphal tips and septa to direct growth, septation, and disease in the human pathogen Aspergillus fumigatus. Here we discovered a novel motif (FMDVF) required for this critical CnaA septal localization, including residues Phe368, Asp370 and Phe372 overlapping the cyclosporine A-cyclophilin A binding domain, CnaB-binding helix and the FK506-FKBP12 binding pocket. Mutations in adjacent residues Asn367, Trp3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
5
0
2
Order By: Relevance
“…Various domains in calcineurin have been implicated for localization and function at the septum. The FMDVF motif that forms a bridge between two known substrate-binding motifs, PxIxIT and LxVP, is required for septal localization and calcineurin function (Juvvadi et al, 2016). Epichlo€ e festucae CnaA also possesses this motif, together with the serine-proline-rich region (SPRR) proposed to be important for hyphal growth and virulence through phosphorylation of the SPRR domain (Juvvadi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various domains in calcineurin have been implicated for localization and function at the septum. The FMDVF motif that forms a bridge between two known substrate-binding motifs, PxIxIT and LxVP, is required for septal localization and calcineurin function (Juvvadi et al, 2016). Epichlo€ e festucae CnaA also possesses this motif, together with the serine-proline-rich region (SPRR) proposed to be important for hyphal growth and virulence through phosphorylation of the SPRR domain (Juvvadi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In Candida albicans, calcineurin is involved in multi-drug resistance (Hameed et al, 2011) and the maintenance of cell wall integrity through the regulation of the chitin synthesis genes chs2 and chs8 (Munro et al, 2007). Studies in Aspergillus fumigatus have demonstrated a crucial role for calcineurin in hyphal elongation and septa formation (Juvvadi et al, 2011(Juvvadi et al, , 2016da Silva Ferreira et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…85,92 Although mutations in functional domains of calcineurin have revealed important residues required for localization and function of calcineurin at the septum, the exact mechanism of how calcineurin regulates septation is still unclear. 93,94 A filamentous fungalspecific serine proline rich (SPRR) linker domain between the CnBBH and CaMBD was also identified in the A. fumigatus calcineurin catalytic subunit. 93 This SPRR was phosphorylated at all 4 clustered serine residues and mutations in this region caused hyphal growth and virulence defects, implicating the importance of calcineurin phosphorylation for its function.…”
Section: Aspergillus Fumigatusmentioning
confidence: 99%
“…Por tanto, la desubicación de la calcineurina en el CAR cuando se encuentra inactiva se debe a otro mecanismo independiente de la regulación del reconocimiento de estos sitios. La zona de unión a la subunidad reguladora en la subunidad catalítica Ppb1 se encuentra próxima a la zona de unión al inhibidor FK506 y a los sitios LxVP presentes en los sustratos (Juvvadi et al, 2016;Roy and Cyert, 2009). Por tanto, una posible explicación sería que la activación de Ppb1 le provocara un cambio conformacional que permitiera el reconocimiento de los sitios LxVP de la paxilina, orientándola correctamente y facilitando su posicionamiento en el CAR.…”
Section: Discusión 1 La Calcineurina Se Localiza En El Anillo De Actunclassified
“…En la subunidad catalítica de la calcineurina de A. fumigatus se ha implicado a la secuencia FMDVF, muy conservada en los hongos, en la unión de la calcineurina a sus sustratos (Juvvadi et al, 2016). La mutación de este dominio en la levadura de fisión provocó la pérdida de la localización de la calcineurina en el CAR, al igual que ocurría en A. fumigatus.…”
Section: Discusión 1 La Calcineurina Se Localiza En El Anillo De Actunclassified